Phase 2 study of intensified chemotherapy and allogeneic hematopoietic stem cell transplantation for older patients with acute lymphoblastic leukemia. Issue 15 (12th May 2016) - Fathi, Amir T.; DeAngelo, Daniel J.; Stevenson, Kristen E.; Kolitz, Jonathan E.; Asch, Julie D.; Amrein, Philip C.; Attar, Eyal C.; Steensma, David P.; Wadleigh, Martha; Foster, Julia; Connolly, Christine; Galinsky, Ilene; et al.
Abstract : BACKGROUND: Outcomes among older patients with acute lymphoblastic leukemia remain poor. This study sought to determine the efficacy of an intensified, multi‐agent approach derived from a Dana‐Farber consortium trial in younger adults for patients older than 50 years (trial identifier NCT00973752). METHODS: The primary endpoint was overall survival (OS) at 1 year. Patients received induction chemotherapy with vincristine, prednisone, doxorubicin, and pegylated asparaginase. Imatinib was incorporated for Philadelphia chromosome–positive disease. After induction, the first consolidation incorporated clofarabine. Patients in remission could proceed to allogeneic hematopoietic cell transplantation (HCT) after induction and consolidation I. Those not receiving HCT went on to receive central nervous system, consolidation II, and continuation phases of treatment. RESULTS: Thirty patients were enrolled: 19 achieved a complete remission (CR) after induction and 1 achieved CR after consolidation I for a CR rate of 67%. Sixteen patients underwent HCT. The proportion surviving at 1 year was 63%, and this met the primary endpoint. The 2‐year OS rate was 52% (n = 30), and the 2‐year disease‐free survival rate was 52% for patients achieving CR (n = 20). There was no survival advantage among those undergoing HCT. Therapy‐related hyperbilirubinemia prompted adjustments and limitations to asparaginase dosing. CONCLUSIONS: Intensified chemotherapy can result in improved outcomes in comparison with historical data. Additional studies of similarly intensive regimens are warranted in this population. Cancer 2016;122:2379–2388 . © 2016 American Cancer Society . Abstract : The intensification of chemotherapy for older patients with acute lymphoblastic leukemia can result in improved outcomes in comparison with historical data. Intensification may be appropriate for sufficiently robust older patients with Philadelphia chromosome–negative acute lymphoblastic leukemia.